Effects of copper model in blended service learning for the enhancement of undergraduate academic achievements and critical thinking - Phakakat, Suphamart; Sovajassatakul, Thanongsak (My University, 2020)
This study is aimed at comparing academic achievements and critical thinking skills between the groups undertaking blended service learning and typical learning. A cluster random sampling was employed to sample 62 students. The experimental and control groups respectively comprised 30 and 32 of them. The instruments were 1) a Copper Model lesson plan, 2) online instructional media on Computer and Information Technology, 3) a critical thinking measurement, and 4) an academic achievement measurement. Data were analyzed using mean (x), standard deviation (SD), and one-way MANOVA. Results concluded that the experimental group with blended service learning achieved higher academic achievements and critical thinking skills than the control group at the.05 significance level.
Keywords: Academic achievement; Blended learning; Copper model; Critical thinking skills; Service learning